The flexible-learning journey: phenomenological investigation of self-efficacy influencing factors among higher education students - Talosa, Arlene D.; Javier, Billy S.; Dirain, Estela L. (Linguistics and Culture Review, 2021)
Philippine higher education has been driven by the urgency of alternative learning modalities from traditional to flexible teaching and learning. Much research has already been embarked on flexible learning. New to the platform, this study purports to document and describe the learning opportunities and influencing factors on the self-efficacy of students in a flexible learning set-up. Using In-depth individual interviews as its method, the qualitative study was administered to higher education students who consented to take part in the study. Findings revealed that self-regulated learning and digital or technological self-efficacy are the two themes found as a learning opportunity with the current learning modality. Personal, Technological, Communication, Home Environment, and Teacher-related are the overarching themes that emerged as influencing factors. The findings of this study have generated several implications for teaching practice, technology experts, and other stakeholders that must be considered very seriously as they represent the opinion of the users of flexible learning.